THE EFFECT OF PEER EDUCATION ON ANEMIA PREVENTION BEHAVIOR AMONG ADOLESCENCE GIRLS AT SENIOR HIGH SCHOOL 05 OF PEKANBARU - Ika Permanasari; Rika Mianna; Yesi Septina Wati (Jurnal Endurance, 2021)
Anemia is one of the most common nutritional deficiency disorders in the community. Adolescent girls are population group that is vulnerable to iron deficiency anemia since they are at puberty which causes high iron loses due to menstruation. In addition, it is exacerbated by lack consumption behavior of foods that contain less iron. One of the anemia prevention can be conducted with behavioral change interventions through peer education. This study aims to determine the effect of peer education on anemia prevention behavior. This was a quasi-experiment with a nonequivalent pretest-posttest with control group. This research was conducted from March-September 2019 in 26 adolescent girls.The sampling technique applied purposive sampling method. Analysis of research data applied an independent sample t test.The results showed that there were significant differences in the two treatment groups with average value of knowledge (p = 0.013), attitude (p = 0.011) and skills (p = 0.032) of adolescent girls in the prevention of anemia as compared to the control group. Peer education is an effective strategy to improve anemia prevention behavior in adolescent’s girls. It is expected that the education program through peers will be further improved and considered as an agenda in student organization activities